Intertidal Euryleptid polyclads and description of a new Stylostomum Lang, 1884 from Maharashtra, India - Pitale, Reshma; Apte, Deepak (Zootaxa, 2019)
The family Euryleptidae, consisting of 19 genera, is as colourful and distinct as the family Pseudocerotidae. Five species of Euryleptidae encountered during surveys in the intertidal rocky shores of Ratnagiri, Maharashtra are presented in the current study. Cycloporus variegatus is new records to India. Cycloporus australis and C. reticulatus are new records to India and reported for the second time after their first formal descriptions in 1982 and 2002 respectively. Eurylepta aurantiaca is a new record to the Indian ocean. The study also describes the new species Stylostomum mixtomaculatum sp. nov. and it is the first report of the genus Stylostomum from the tropical realms. Since Stylostomum and Acerotisa are known to be closely allied genera, efforts have been made to review their species assemblages and throw light on the existing ambiguities within the available information. With this report, the number of euryleptid species from Indian waters increases to eight.